2018
DOI: 10.1002/suco.201800058
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behavior and optimization of air‐entrained reinforced concrete, incorporating microsilica

Abstract: Nowadays, corrosion evaluation of steel embedded in reinforced concrete (RC) plays an important role in repair, protection and maintenance of RC structures. Air‐entraining agent (AEA) and microsilica (MS) are among the most important admixtures, which affect the corrosion rate (CR) of RC. Specifically, 12 mix designs incorporating different contents of AEA (ie, 0, 0.7, 1.4, 2.1, 2.9, and 3.6% by weight), half with 10% MS, were constructed. The corrosion behavior of RC specimens after exposure to 3.5% NaCl envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Authors concluded that 6% of microsilica and 1,5% of nanosilica improves strength characteristics, electric impedance and reduces capillary intake. Results of our research actually coincide with research of other scientists [2][3][4][7][8][9]. Reducing of concrete consumption by its substitution by microsilica, has a positive influence to physico-chemical characteristics of concrete.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Authors concluded that 6% of microsilica and 1,5% of nanosilica improves strength characteristics, electric impedance and reduces capillary intake. Results of our research actually coincide with research of other scientists [2][3][4][7][8][9]. Reducing of concrete consumption by its substitution by microsilica, has a positive influence to physico-chemical characteristics of concrete.…”
Section: Discussionsupporting
confidence: 88%
“…The theoretical basis received of work becameof group the research of national isand foreign scientists is was setdevoted to structuremarkcement compositionChernishovaand problems of modification of uniquehydrational systemssolidification with the use of ismineral and chemicalprocessadditives. Based on works of Ailer R., Kaprielov S.S. [1,2] corresponding performance of amorphous quartz in water, acid and alkaline environment, and in the view of information corresponding cement modification, where the complex additives containing particles of SiO2 similar in crystallochemical structure are preferable, it could be considered that chemical activation of microsilica is cheap and upcoming trend for modification of structure of cement rock and cement on its basis. Analysis of literary sources indicated that one of effective pozzolanic active mineral additive for cement matrix and cement on its basis, is microsilica -powdery waste of ferroalloy industry containinf SiO2 not less than 91% [5,6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The cementitious content of all mixes is maintained constant using a constant dose of 2.5% high range water reducer (superplasticizer) by weight of cementitious materials along with a fixed 0.4 water/cementitious ratio. Mechanical properties of cement mortars are dependent on many parameter, and according to the previous literature properties are influenced by the water/cement ratio (W/C) [21], aggregate/cement ratio (A/C) [22,23], age [24,3], and admixture dose [25,26]. Tension specimens include T in their ID.…”
Section: Test Specimensmentioning
confidence: 99%